Vitamin D supplementation is beneficial in improving the prognosis of patients with acute respiratory failure in the intensive care unit: a retrospective study based on the MIMIC-IV database - Hu, Song; He, Qian; Xie, Jun; Liu, Hui; Zhou, Rong; Li, Chong (Frontiers in Medicine, 2023)
Background Vitamin D plays a critical role in the regulation of multiple physiological pathways. Vitamin D deficiency may be a risk factor for life-threatening clinical conditions. Several studies have found that vitamin D supplementation in critically ill patients improves prognosis. The purpose of this study was to determine the association between vitamin D and the prognosis of patients with acute respiratory failure (ARF). Methods In this retrospective cohort study, we collected clinical information of ARF patients from the Medical Information Mart for Intensive Care IV (MIMIC-IV) version 2.0 database. The outcome of this study was in-hospital mortality, intensive care unit (ICU) mortality. Patients were divided into the no-vitamin D and vitamin D groups according to whether they received supplementation or not. The correlation between vitamin D and outcome was examined using Kaplan–Meier (KM) survival curves, Cox proportional risk regression models and subgroup analyses. Propensity-score matching (PSM) was used to ensure the robustness of our findings. Results The study finally included 7,994 patients with ARF, comprising 6,926 and 1,068 in the no-vitamin D and vitamin D groups, respectively. The Kaplan–Meier survival curve indicated a significant difference in survival probability between the two groups. After adjustment for a series of confounders, the multivariate Cox proportional hazards models showed that the hazard ratio (95% confidence interval) values for in-hospital and ICU mortality in the no-vitamin D group were 1.67 (1.45, 1.93) and 1.64 (1.36, 1.98), respectively. The results of propensity score-matched (PSM) analysis were consistent with the original population. In the subgroup analysis, Vitamin D supplementation was associated with lower in-hospital mortality in patients with higher clinical scores (SOFA score ≥ 8, OASIS ≥ 38). Conclusion Our study concluded that Vitamin D supplementation may reduce in-hospital and ICU mortality in patients with ARF in the ICU. There may be a beneficial effect on in-hospital mortality in patients with higher clinical scores. Additional randomized controlled trials are needed to follow up to confirm the relationship between vitamin D supplementation and ARF.